Food-variety-focused labelling does not increase ideal portion size, expected fullness or snack intake. (April 2019) - Embling, Rochelle; Price, Menna; Lee, Michelle; Wilkinson, Laura
Highlights: Foods were displayed with either a high or low variety label or no label. The 'variety-labelling' manipulation had no effect on ideal portion size. The 'variety-labelling' manipulation had no effect on expected fullness. The 'variety-labelling' manipulation had no effect on snack intake. Bayesian analyses suggested no effect of a variety-labelling manipulation. Abstract: As greater food variety has been shown to increase intake and is associated with a higher BMI, interventions that modify the effects of food variety have implications for combatting obesity. Previous research has shown that labelling a food with 'high variety' flavour-specific labels can reduce an individual's satiation whilst eating. We were interested in whether the effects of 'variety labelling' would also be observed on portion size selection and ad libitum food intake. Therefore, two studies were conducted to explore the effects of labelling foods with different levels of variety on ideal portion size, ratings of expected fullness, and actual intake. In Study 1 (N = 294), participants viewed images of a range of foods that were presented with either high variety labels (descriptions of within-food components), low variety labels (general names of food items), or no label in an online survey. They selected their ideal portion size and rated their expected fullness for each food. In Study 2 (N = 99), they also consumed one of these foods ad libitum in the laboratory. It was hypothesised that foods presented with high variety labels would have an increased ideal portion size, reduced expected fullness, and increased intake compared to foods presented with low variety labels or no label. Our findings failed to support these predictions, and we found no evidence of an effect of variety labelling on ideal portion size, expected fullness or food intake. These findings highlight the importance of considering the ecological validity of consumer research studies.